Saddle pulmonary embolism in the setting of COVID-19 infection: A systematic review of case reports and case series - Hassan Choudry (12217767) (2023)
Saddle pulmonary embolism (SPE) is a rare type of pulmonary embolism that can lead to hemodynamic compromise causing sudden deaths. Due to a dearth of large prospective studies in this area, little is known regarding the epidemiology, and prognosis and factors affecting the latter for COVID-19-associated SPE. We aimed to describe COVID-19-associated SPE and quantify and compare mortality and factors affecting mortality among the cases. We included a total of 25 publications with a total of 35 cases. The average age was 45 ± 16.3 years with 11 females and 24 males. Dyspnoea (82.5%), orthopnoea (43.5%), and cough (43.5%) were the most common symptoms, and obstructive shock was present in five (21.7%) patients. The average reported oxygen (O2) saturation was 85.8% ± 11.9 mm Hg. Hypertension (26.1%), diabetes (21.7%), and deep vein thrombosis (21.7%) were the most commonly reported comorbidities. Right heart strain was recognized in seven (30%) patients on electroencephalogram (S1QIIITIII) and 12 (52.2%) patients on echocardiogram. Anticoagulation, thrombolysis, and percutaneous intervention were tried in 21 (91.3%), 13 (56.5%), and 6 (26.1%) cases, respectively. Despite the aggressive management, 2 of 25 (8.7%) patients died in our smaller case report cohort. We conclude that despite aggressive management modalities, the mortality of SPE remains high in COVID-19. Other Information Published in: Open Medicine License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1515/med-2023-0724